Comprehensive Review of the Evolving Roles of Health Technicians in Clinical and Laboratory Settings - Alaqeel, Fatmah Saleh; Alalawi, Wejdan Abdullah; Khomaise, Osama Ahmed; Aljohani, Mashel Bader; Almuhammadi, Sarah Saeed; Alrashidi, Reuof Saleh; Aboaifah, Zhrah Mosa; Khoumaeys, Adnan Ahmed; Mohammad, Badr Hamed Yar; Al Ahmedi, Fahad Salaman Saad (Journal of Ecohumanism, 2024)
Health technicians are members who are a core factor of a healthcare team, and they are progressively integrating themselves in their roles because of the advancements in medical technology, the growth of healthcare functions, and characteristics of clinical as well as laboratory environments. This review seeks to discuss the shift of responsibilities of health technicians, especially in clinical and laboratory settings, the technology involved, and the implications of all of these to the healthcare industry. The literature review focuses on the increasing roles of specialized training of the health technicians, the efficiency of the teamwork approach, and profiles of utilizing technicians as pivotal components to better healthcare for patients, the accuracy of diagnosing diseases, and improving the overall effectiveness of healthcare systems.